Atypical ‘Granulomatosis with Polyangiitis’ Presenting with Epistaxis - Akter, Sumaiya; Ahasan, HAM Nazmul; Islam, Quazi Tarikul (Journal of Medicine, 2021)
Granulomatosis with polyangiitis (GPA) is a systemic necrotizing vasculitis involving small and mediumsized blood vessels and granulomatous inflammation of upper and lower respiratory systems and/or renal system. In the limited form of GPA, there is no systemic involvement of disease with sparing of kidneys. Herein, we report a case of 37-year-old male who was diagnosed as ethmoidal polyposis clinically. Ethmoidal tissue biopsy granulomatous angiitis. Diagnosis of GPA was made which was substantiated by antineutrophil cytoplasmic antibody (ANCA) positivity. This was a case of GPA involving only upper respiratory system. The early diagnosis and initiation of treatment are critical for improved survival of patients with GPA. Tissue biopsy is necessary for the diagnosis of GPA. J MEDICINE JAN 2021; 22 (1) : 81-83